Female sexual dysfunction as an adverse effect of drugs: a narrative review - Piha, Mikael O. W.; Kero, Katja; Tornio, Aleksi (Elsevier BV, 2025)
Sexual adverse effects of drugs are common and can compromise adherence to pharmacotherapy. Drugs can disrupt any or all phases of the sexual response cycle, potentially causing significant distress, which can amount to clinically relevant sexual dysfunction. Psychotropic and neurotropic agents are the best-characterised culprits in drug-related sexual dysfunction in females, although sexual dysfunction has been defined in various ways in the relevant literature. Specifically, serotonergic antidepressants, prolactin-increasing antipsychotics, long-term opioid therapy, and enzyme-inducing antiepileptics are associated with decreased desire, arousal dysfunction, orgasmic dysfunction, and more. In addition, progestin-containing contraceptives, antioestrogenic drugs, and beta blockers appear to increase the risk of sexual dysfunction. Possible mechanisms by which drugs interfere with sexual functions include alterations in neurotransmitter systems, increases in prolactin levels, increased sedation, and inhibition of the hypothalamic-pituitary-ovarian axis. Many medical conditions themselves can also cause sexual symptoms, and these are difficult to distinguish from pharmacological sexual adverse effects. However, different drugs for the same diseases can have substantially different sexual safety profiles, which often allows the clinician to choose a less-offending alternative. In some cases, drugs can exert even long-term adverse effects on sexual function. Therefore, sexual adverse effects must be taken into consideration when weighing the benefits and risks of different treatment modalities.